Generation Of Vortices In Air Flow Throuh Plates In Tandem - Abdul Rashid, Nordalilah (Universiti Sains Malaysia, 2000)
My final year project entitled generation of vortex layer in tandem plates is a project of simulation using ANSYS/FLOTRAN which will develop the vortex layer by interactive.The software is capable of inspecting the flow trend with the specification given.Besides the interactive method,it also capable of simulating through command that is taken from a file compiled .This method is very useful for a long and repititive simulation .ANSYS is not only a software for the fluid mechanics, it can be used for the mechanical or thermal. In this project, a model of two plates in tandem position will be simulated to see how the formation and genaration of vortex layer when a fluid flow through the two plates, in tandem, with different angles and different fluid velocity .Here, the fluid is the air and the degree at which the two plates rotates is from 00 ,40,80,120 while the velocity is changing from 1m/s, 3,m/s,18m/s and 36m/s. Observation on how the formation of vortex, where, at what angle and velocity is done using the vector and contour of velocity and pressure that is produced by the simulation done by the software.